2011
DOI: 10.1258/msl.2011.010152
|View full text |Cite
|
Sign up to set email alerts
|

Mesiodistal width of canines: a tool for sex determination

Abstract: Teeth, in the living as well as the dead, are the most useful objects in the field of forensic investigation. Their ability to survive in situations like mass disasters makes them important tools in victim identification. Though the morphology and structure is similar in both men and women, there are subtle differences. Variation in dental size can give a clue about differences between the sexes. Many authors have measured the crowns of teeth in both men and women and found certain variations. Canines, reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 10 publications
(13 reference statements)
1
23
1
5
Order By: Relevance
“…[1] Dental anthropology is concerned with the study of morphological variation (dental morphological features) and metrics of the dentition of human populations over time (prehistoric and modern) and space (ethnic influences) and their relation with the processes of adaptation and dietary changes that led to the evolution of the dental system and the human race. [2] For forensic and archeological excavations, every time it is not possible to get all the bones of an individual and hence the collected skull and teeth will provide an identification.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Dental anthropology is concerned with the study of morphological variation (dental morphological features) and metrics of the dentition of human populations over time (prehistoric and modern) and space (ethnic influences) and their relation with the processes of adaptation and dietary changes that led to the evolution of the dental system and the human race. [2] For forensic and archeological excavations, every time it is not possible to get all the bones of an individual and hence the collected skull and teeth will provide an identification.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the most dimorphic tooth is the mandibular canine and it can be of immense medicolegal use in identification [3, 5, 8]. The measure of the coronal tissue proportions of permanent mandibular canines suggests that males have heavier teeth and more dentin than their female counterparts [1].…”
Section: Introductionmentioning
confidence: 99%
“…Many researches were done to identify the genders using the maxillary and mandibular canines. They depended on the mesio-distal dimension of these teeth (5,6) and in many articles on the intercanine width in addition to the mesio-distal width to get the canine index and standard canine index (2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) . Other researches studied the bucco-lingual dimension of teeth (18,19) , height of tooth (3) and permanent maxillary first molar (20) as a base for gender identification.…”
Section: Introductionmentioning
confidence: 99%